TNI Bill and Regional Autonomy: Implications for Central-Regional Relations in Security Management - Resma Bintani Gustaliza; Darsis Humah; Bonefasius Bao (Pt. Anagata Sembagi Education, 2025)
Following the 1998 reforms, Indonesia experienced a significant transformation in the security sector, marked by the elimination of the dual function of the Indonesian Armed Forces (ABRI) and the strengthening of civilian supremacy. However, the current discussion of the Draft Law on the Indonesian National Armed Forces (RUU TNI) has raised concerns about the return of military dominance in civil affairs through military operations other than war (OMSP). This study analyzes the potential impact of the RUU TNI on central-regional relations in security management. Using a qualitative descriptive approach through literature study, this study examines the normative provisions in the RUU TNI and compares them with the principles of democratization and decentralization. The findings show that expanding the role of the TNI in domestic affairs without a civilian oversight mechanism and coordination with local governments has the potential to blur the boundaries between civil defense and security functions, weaken regional autonomy, and create institutional tensions. Central dominance through the military also increases the risk of human rights violations and reduces accountability for security governance. Therefore, the revision of the RUU TNI needs to consider the principles of civilian supremacy, military professionalism, and regional participation in national security policies to prevent the decline of democratic reforms and maintain inclusive and equitable national integration.